A new energy efficient single-stage flash drying system integrated with heat recovery applications in industry. Issue 5 (3rd April 2020) - Ishaq, Haris; Dincer, Ibrahim
Abstract: A new system developed here conducts the thermal management of the flue gas from the cement industry and employs this heat for the drying of raw materials before reaching to the preheating section. As of now, an additional amount of heat is used to provide the drying section with hot air while this proposed configuration recovers the heat from the same plant and employs it for drying purpose. This approach also results in cost saving as this configuration decreases the cost of heating the ambient air to provide the drying section with hot air. The entire system is simulated using the Aspen Plus industrial software. A comprehensive thermodynamic analysis is conducted for each component of the proposed system keeping more focus on the drying section. Numerous parametric and sensitivity studies are conducted to investigate the system performance, pressure drop and raw materials drying. The energy and exergy efficiencies of the drying process are found to be 55.6% and 24.17%. On the basis of the present results achieved, one can say that this novel configuration can be proved as a benchmark for the cement industry and has the capability to reduce the cost as well.